MIGHT PIEZO-ICSI BE AN ALTERNATIVE TO CONVENTIONAL ICSI IN PATIENTS WITH LOW FERTILIZATION RATES? - Yuceturk, Aysen; Cakiroglu, Yigit; Karaosmanoglu, Ozge; Korun, Zeynep Ece Utkan; Yazicioglu, Caglar; Tiras, Bulent (ELSEVIER SCIENCE INC, 2023)
79th Scientific Congress of the American-Society-for-Reproductive-Medicine (ASRM), New Orleans, LA, OCT 14-18, 2023